2020
DOI: 10.31083/j.jin.2020.03.175
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between recovery of motor function and neuropsychological functioning in cerebral infarction patients: the importance of social functioning in motor recovery

Abstract: Impaired motor function is a common disabling sequela after stroke. It is closely associated with the patient's quality of life and independence. Neuropsychological dysfunctions also frequently occur in stroke patients. In this paper, we evaluate the relationship between the recovery of motor function and neuropsychological functions, including cognition, language, emotion, behavior, personality, and social interaction, to provide appropriate and effective therapy for stroke patients. Motor function, neuropsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The studies in recent years have shown that the combination of TCM and Western medicine can accelerate the neurological recovery. According to TCM, cerebral infarction belongs to the category of “apoplexy” and is usually caused by qi stagnation and blood stasis, so the treatment for it should focus on promoting qi to activate blood, so as to relieve the phlegm-blood stasis and obstruction of meridians and alleviate the disturbance of consciousness and clumsy physical activities [ 21 ]. Acupuncture is a common TCM intervention, and the acupoints in this study can cooperate with each other to regulate yin and yang, and the patients' neurological functions were recovered to some level and their limb functions were improved after the acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in recent years have shown that the combination of TCM and Western medicine can accelerate the neurological recovery. According to TCM, cerebral infarction belongs to the category of “apoplexy” and is usually caused by qi stagnation and blood stasis, so the treatment for it should focus on promoting qi to activate blood, so as to relieve the phlegm-blood stasis and obstruction of meridians and alleviate the disturbance of consciousness and clumsy physical activities [ 21 ]. Acupuncture is a common TCM intervention, and the acupoints in this study can cooperate with each other to regulate yin and yang, and the patients' neurological functions were recovered to some level and their limb functions were improved after the acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired motor function is a common disabling sequela following stroke. 30 Ischemic stroke severely impacts the quality of life and independence of survivors. 31 Quality of life questionnaires are used to describe the impact of aphasia on stroke survivors' life.…”
Section: Discussionmentioning
confidence: 99%
“…The following demographic and clinical data were collected when patients were transferred to the rehabilitation unit (8–30 days after stroke onset): age, sex, type of stroke (ischemic/hemorrhagic), modified Brunnstrom classification (MBC), functional ambulation score (FAC), and Medical Research Council (MRC) score for muscle strength of shoulder abductor, elbow flexor, finger flexor, finger extensor, hip flexor, knee extensor, and ankle dorsiflexor of the affected side [16, 17]. We selected these input variables because they are most commonly and easily collected when stroke patients are admitted or visit the hospital for rehabilitation.…”
Section: Methodsmentioning
confidence: 99%